Assessment of Teacher's Knowledge of Computer Software for Teaching Islamic Studies in Senior Secondary Schools in Kwara State, Nigeria - Owoyale-Abdulganiy, Ibrahim Solahudeen; Abdur-Rafiu, Jamiu; Abdulrazaq, Abdulraheem (Kompetensi: Jurnal Pendidikan dan Pembelajaran, 2024)
The study examined availability and accessibility of computer software in teaching of Arabic in Secondary Schools in Kwara State. To examine the accessibility of computer software for teaching Islamic Studies in Senior Secondary Schools in Kwara state. Two research questions and two research hypotheses were formulated and tested at 0.05 level of significance. This study adopted a descriptive survey research design. The target population was 360 Islamic Studies Teachers in 50 Senior Secondary Schools. The sample was 186 Islamic studies Teachers in Senior Secondary schools purposively selected for the study. The researcher’s self-designed instrument titled “Accessibility and Utilisation of the Computer Software Questionnaire (AUCSQ) was used to collect data from the respondents. The reliability coefficient of the AUCSQ was 0.86. Frequency and Percentage were used to present the demographic information of the respondents and to answer the research questions while the Pearson Product Moment Correlation Coefficient was used to test hypotheses. The study revealed a significant correlation between the availability of computer software and the teaching of Islamic Studies in Senior Secondary Schools in Kwara State. The study found a significant negative correlation between the accessibility of computer software and the teaching of Islamic Studies in Senior Secondary Schools in Kwara State. The study found that the lack of access to computer software negatively impacts the teaching of Islamic studies in secondary schools in Kwara State. It recommended that school management should provide adequate computer software for teachers and that Islamic studies teachers should acquire computer skills for easy access to the software.